Diiodine-Mediated Oxidative Reaction for the Construction of Imidazo[1,5-a]pyridines under Metal-Free Conditions - Su, Kexin; Qin, Mingda; Chen, Yongxin; Liu, Yafeng; Tian, Yuan; Chen, Baohua (Synlett, 2020)
An efficient and general protocol has been developed for preparing imidazo[1,5-a]pyridines in moderate to excellent yields by an I2-mediated sequential dual oxidative C(sp3)–H amination of ethyl pyridin-2-ylacetates with benzylamines. The metal- and peroxide-free reaction involves oxidative dehydrogenation and two C–N couplings.
Keywords: imidazopyridines; metal-free synthesis; amination; benzylic amines; ethyl pyridinylacetates